The sigma-Hole Coulombic Interpretation of Trihalide Anion Formation - Clark, Timothy; Murray, Jane S.; Politzer, Peter (ChemPhysChem, 2018)
It is shown that the interactions of dihalogen molecules XY with halide anions Z(-) to form trihalide anions (XYZ)(-) can be satisfactorily described as Coulombic, involving the sigma-holes on the atoms Y, but only if polarization is taken into account. We have approximated the polarizing effect of the halide anion Z(-) by means of a unit negative point charge. The CCSD/aug-cc-pVTZ computed interaction energies Delta E correlate well with the most positive electrostatic potentials associated with the induced sigma-holes over a Delta E range of -12 to -63 kcal mol(-1). The (XYZ)(-) anions are more stable when the central atom is the largest, as has been observed, because the central atom is then the most polarizable, making the electrostatic potential associated with its sigma-hole more positive.
Keywords: trihalide anions; Coulombic interactions; sigma-holes; polarization; electrostatic potentials